Efektivitas Jus Jeruk, Tomat, dan Madu untuk Mengatasi Anemia pada Ibu Hamil - Melva Simatupang; Franciska Debora Simanjuntak (FORIKES, 2022)
The high incidence of anemia in pregnant women is closely related to the lack of intake of nutrients, especially foods that can help absorb iron such as orange juice, tomatoes and honey. This study aims to determine the effectiveness of giving orange juice, tomatoes and honey to treat anemia in pregnant women. The literature used is published in 2016-2021, obtained from Google Scholar, PubMed, ScienceDirect, Elsevier, with an experimental design. Of the 25 articles reviewed regarding giving orange juice, there was the largest increase in hemoglobin levels of 0.97 g/dl; on giving tomato juice, the highest hemoglobin was 2.20 g/dl; in giving honey, the highest hemoglobin was 2.27 g/dl. It was concluded that giving orange juice, tomatoes or honey is effective for increasing hemoglobin levels in pregnant women, but giving honey is more effective for treating anemia.Keywords: anemia; orange juice; tomato juice; honey ABSTRAK Tingginya kejadian anemia pada ibu hamil erat kaitannya dengan kurangnya asupan zat gizi, khususnya makanan yang dapat membantu penyerapan zat besi seperti jus jeruk, tomat, dan madu. Studi ini bertujuan untuk mengetahui efektivitas pemberian jus jeruk, tomat, dan madu untuk mengatasi anemia pada ibu hamil. Literatur yang digunakan adalah terbitan tahun 2016-2021, yang didapatkan dari Google Scholar, PubMed, ScienceDirect, Elsevier, dengan desain eksperimen. Dari 25 artikel yang telah di-review mengenai pemberian jus jeruk, terdapat peningkatan kadar hemoglobin terbesar sebanyak 0,97 g/dl; pada pemberian jus tomat, hemoglobin terbesar adalah 2,20 g/dl; pada pemberian madu, hemoglobin terbesar adalah 2,27 g/dl. Disimpulkan bahwa pemberian jus jeruk, tomat, atau madu efektif untuk meningkatkan kadar hemoglobin pada ibu hamil, tetapi pemberian madu lebih efektif untuk mengatasi anemia. Kata kunci: anemia; jus jeruk; jus tomat; madu